2002
DOI: 10.4049/jimmunol.168.5.2493
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Dendritic Cells, But Not Macrophages, in Patients with Sepsis

Abstract: Dendritic cells (DCs) are a group of APCs that have an extraordinary capacity to interact with T and B cells and modulate their responses to invading pathogens. Although a number of defects in the immune system have been identified in sepsis, few studies have examined the effect of sepsis on DCs, which is the purpose of this study. In addition, this study investigated the effect of sepsis on macrophages, which are reported to undergo apoptosis, and MHC II expression, which has been noted to be decreased in sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
241
2
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(273 citation statements)
references
References 24 publications
18
241
2
10
Order By: Relevance
“…A possible explanation of mDC loss may be the increased apoptosis rate which we found in septic PBDC with respect to controls. These observations are consistent with previous observation indicating that DC in lymph nodes and spleen undergo caspase-mediated apoptosis during experimental sepsis, (26,28) and that spleens from patients who died of sepsis exhibited extensive apoptotic DC loss (33).…”
Section: Dendritic Cells In Severe Sepsissupporting
confidence: 82%
See 1 more Smart Citation
“…A possible explanation of mDC loss may be the increased apoptosis rate which we found in septic PBDC with respect to controls. These observations are consistent with previous observation indicating that DC in lymph nodes and spleen undergo caspase-mediated apoptosis during experimental sepsis, (26,28) and that spleens from patients who died of sepsis exhibited extensive apoptotic DC loss (33).…”
Section: Dendritic Cells In Severe Sepsissupporting
confidence: 82%
“…The procedures followed were in accordance with the ethical standards of the institutional committee on human experimentation and with the Helsinki Declaration of 1975, as revised in 2000. Severe sepsis and septic shock were defined according to the 1992 Consensus Conference of the American College of Chest Physicians/Society of Critical Care Medicine (33). Patients were enrolled in the study in the presence of a documented or suspected infection and sepsis-induced failure of at least two organs or systems that lasted no longer than 48 h at the time of screening.…”
Section: Materials and Methods Patients And Study Designmentioning
confidence: 99%
“…Forty to 50% losses of both total (CD11c high ) and lymphoid (CD8␣ ϩ ) DC populations were seen within 24 h. Similar results have been observed by others (11,12), and Hotchkiss et al (13) have reported an increased loss of DCs from the spleens of patients who had died from sepsis. Furthermore, the intrapulmonary installation of bone marrow-derived DCs prevented lethal Aspergillosis infection in septic animals (14), suggesting a functional role for DCs in opportunistic fungal infections in the lung during sepsis.…”
supporting
confidence: 77%
“…Concominantly, there is substantial depletion of DC along with increased levels of circulating Treg [31][32][33]. However, the mechanism of how DC apoptosis can contribute to immunosuppression in sepsis is unclear.…”
Section: Discussionmentioning
confidence: 99%